PENGARUH PENGGUNAAN SILASE ISI RUMEN SAPI DALAM KONSENTRAT TERHADAP KONSUMSI, KECERNAAN DAN EFISIENSI PROTEIN RANSUM PADA TERNAK KAMBING LOKAL JANTAN (Effect of Using Cow Rumen Silage in Concentrate on Consumption, Digestibility, and Ration Protein.....) - Seran, Maria P. S. E. P; Lazarus, Edwin J. L.; Wie Lawa, Emma D.; Hilakore, Maritje A. (JURNAL NUKLEUS PETERNAKAN, 2024)
Concentrate is needed as additional feed to supplement deficiencies in forage and to support optimal growth and productivity of goats. The problem is that concentrate source materials are expensive, so to anticipate this problem, cow rumen waste is used as an alternative feed ingredient in concentrate. This study aimed to evaluate the use of cow rumen silage as an alternative feed ingredient in concentrates on crude protein consumption and digestibility and efficiency protein ratio in local male goats. The study was carried out in the laboratory goat pen Faculty Field Farm Maritime Affairs and Fisheries Nusa Cendana University Research was done in an experimental use Completely Randomized Design (CRD), consisting of 4 treatments and 5 replications, namely T0: Kume grass hay 70%+30% Concentrate (without silage containing cow rumen contents), T1: Kume Grass hay 70%+30% Concentrate (concentrate containing 10% silage cow rumen contents), T2: Kume Grass hay 70%+ Concentrate 30% (concentrate containing 20% silage cow rumen contents) and T3: Kume Grass Hay 70%+ Concentrate 30% (concentrate containing 30% silage cow rumen contens). Data obtained was analyzed using Analysis Of Variance (ANOVA). Analysis shows that giving silage contents of the cow's rumen content up to 30% effect no significant (P>0.05) to crude protein consumption, crude protein digestibility, and efficiency protein ratio. It was concluded that using concentrate with cow rumen contents in goat rations at 30% does not significantly affect to protein utilization by local male goats.